2023
DOI: 10.18295/squmj.4.2022.029
|View full text |Cite
|
Sign up to set email alerts
|

Cilia Ultrastructure Associated with Primary Ciliary Dyskinesia in Omani Patients

Abstract: Objectives: Primary ciliary dyskinesia (PCD) is a disorder affecting the structure and function of motile cilia. Transmission electron microscopy is one method that can be used to examine ciliary ultrastructure in airway biopsies. Although the role of ultrastructural findings in PCD has been described in the literature, this role has not been well studied in the Middle East or, by extension, Oman. This study aims to describe ultrastructural features in Omani patients with high suspicion of PCD. Methods: This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
0
1
Order By: Relevance
“…Regarding TEM findings, in contrast to the current study that showed ODA loss and MTD + IDA loss to be equally the most common hallmark defects, ODA + IDA loss was the most common hallmark defect reported in previous studies in the Kingdom of Saudi Arabia (KSA), Oman, and Iran 32–34 . ODA absence as a Class 1 hallmark defect was not reported among the Iranian cohort 34 …”
Section: Discussioncontrasting
confidence: 99%
“…Regarding TEM findings, in contrast to the current study that showed ODA loss and MTD + IDA loss to be equally the most common hallmark defects, ODA + IDA loss was the most common hallmark defect reported in previous studies in the Kingdom of Saudi Arabia (KSA), Oman, and Iran 32–34 . ODA absence as a Class 1 hallmark defect was not reported among the Iranian cohort 34 …”
Section: Discussioncontrasting
confidence: 99%